Screw Fixation of Lateral Condyle Fractures: Results of Treatment. Issue 8 (December 2015) - Shirley, Eric; Anderson, Mary; Neal, Kevin; Mazur, John
Abstract : Background: Fixation of lateral condyle distal humeral fractures has traditionally been achieved with K-wires. Screw fixation provides the advantage of compression across the fracture site, but the results of screw fixation and risk of iatrogenic physeal damage are not well defined. This study was designed to evaluate the efficacy of screw fixation for lateral condyle fractures. Methods: A retrospective study of patients with lateral condyle elbow fractures treated using screw fixation at a single institution was undertaken. Patients 12 years and younger with isolated fractures were included. Clinical notes were examined for residual symptoms, alignment, range of motion, and complications. Radiographs were reviewed for healing and growth arrest. Results: Ninety-six patients who were treated over a 7-year period met inclusion criteria. Mean patient age was 5.8 years (range, 2 to 12 y). Fifty-four patients required open reduction; 42 patients underwent a closed reduction. Mean follow-up was 28.1 weeks (range, 4.9 to 417 wk). The overall complication rate was 19% and was 5% when lateral overgrowth was excluded as a complication. Initial fracture union was achieved in 99% of patients. One patient required revision fixation with a bone graft. Hardware was symptomatic with prominence or loss of flexion in 4% of patients. There were no cases of growth arrest or alterations of the carrying angle. For patients with final follow-up >12 months, the mean extension loss was 2 degrees (range, 0 to 25 degrees) and the mean loss of flexion was 8 degrees (range, 0 to 25 degrees). Conclusion: Screw fixation of lateral condyle fractures results in satisfactory union with a low risk of complications at early follow-up. Level of Evidence: This study was a retrospective case series performed to investigate the results of treatment, level IV.